2020
DOI: 10.3390/su12041316
|View full text |Cite
|
Sign up to set email alerts
|

Expert Opinion Dimensions of Rural Landscape Quality in Xiangxi, Hunan, China: Principal Component Analysis and Factor Analysis

Abstract: Scholars and planning/design professionals are interested in the quantitative, metric properties influencing the quality and assessment of rural landscape space. These metrics are important for guiding rural planning, design, and construction of cultural rural environments. Respondents and metrics from four sampled villages (Qixin, Hangsha, Yanpai Xi, and Lvdong) in the Xiangxi District of Hunan Province in China were examined, employing statistical principal component analysis and factor analysis methods to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The intent is not to show which is better, but rather to identify similarities and differences. The plots can depict an educational univers in a manner similar to other types of plots [29][30][31][32][33][34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intent is not to show which is better, but rather to identify similarities and differences. The plots can depict an educational univers in a manner similar to other types of plots [29][30][31][32][33][34].…”
Section: Methodsmentioning
confidence: 99%
“…stated Dr. Burley. With this basic analytic tool (PCA), other kinds of studies related to garden design, cemeteries, cultural heritage landscapes, and paintings have been examined by those working with Dr. Burley [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Economic benefits are assessed by the evidence-based design anchored in quantitative performance assessment of landscape design [9]. The results obtained by the principal component analysis and factor analysis methods revealed that the specific character and unique landform of landscape can be quantitatively described to underline its specific differences from other nearby settlements [10]. As stated by the international group of researchers, analysis of key factors for environmental sustainability reflecting on the traditional architecture reveal that the priority factor is creating engagement between buildings and other urban and natural systems as landscape [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While analysing landscape quality components researchers emphasise such intangible cultural factors as folk customs, inheritance of folk art, etc. [10] Sustainable performance and operation of a project is one of its key aspects. Analysing sustainability of an urban district requires more data processing than that for a single building taken in isolation from the processes in its surroundings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Approximately half the world’s population lives in rural areas [ 1 ], the outdoor spaces of which have great functional importance in the residents’ lives. Rapid urbanisation has disturbed the rural outdoor environment [ 2 ]. In the past, rural planning has primarily considered spatial layout, culture, ecology, and other village functions [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%